Valuation of Intellectual Property Rights - Copyrights to Audiovisual Works: An International Comparison of Copyright Management Organizations - Paweł KOSSECKI; Oguzhan AKIN; Jacek WACHOWICZ (Communications of International Proceedings, 2021)
Defining a method for calculating the value of copyrights and related rights is crucial for the audiovisual works as well as the media industry in the climate of the new economy. It is a cross-disciplinary problem, as it reflects both legal aspects of streaming and business strategic management requirements. Existing monopolies rule the valuation practices with no transparency which limits the heterogeneity of markets. One of the ways to investigate proper valuation is the international comparison method across different markets. The objective of this paper is to show the position that Copyright Management Organizations (CMOs), which may be considered as entrepreneurs with a monopolistic position on a given market, hold on the local markets and compare those markets, reflecting local fees to economic factors. The formalism and methods of multivariate comparative statistical analysis has been facilitated to recognize and classify the similarities and differences of CMOs’ markets within 22 European countries. This research, enabled the identification of four main clusters defined by economic factors, including those concerning CMO set values. They show not only a geographical distinction, but also a socio-economic ones. Its outcomes may help common understanding in fee calculation methods adjusted to national markets, among others, to avoid legal disputes and incoherence in the matter.
Keywords: Copyright Management Organizations; copyrights; audiovisual works; comparison